Korelasi dan Kontribusi Asesmen Portofolio Terhadap Habits Of Mind Siswa SMAN Kota Pekanbaru - Nurkahairo Hidayati; Tengku Idris (Universitas Lampung, 2017)
This research was conducted with the aim to know the correlation and contribution of portfolio assessment to the habits of mind of SMAN Pekanbaru students. The research was conducted on the students of class XI at six SMAN Pekanbaru City. The research design used was